I can make a difference and so can you! - Flynn, Nicole (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2017)
Nicole Flynn is a twenty-four year old advocate, artist and athlete with Down syndrome. Nicole began public speaking at eight years old when she would talk to various groups - such as classes at the University of Toronto and at Humber, Centennial and Seneca Colleges - about her achievements and goals. As she got older, she started to speak seriously about people who are different and how they want to be treated with equality. Nicole is also passionate about saving the environment. This speech was written for a Youth to Youth Summit in September, 2017.